Enhancing Students’ Critical Thinking in Writing Through Group Investigation Strategy Assisted by Digital Story Board Media: A CLASSROOM ACTION RESEARCH - Ginting, Pirman; Hasnah, Yenni; Utami, Dinda Sari (IJET (Indonesian Journal of English Teaching), 2021)
This research deals with classroom action research aiming to enhance students' critical thinking in writing through the application of group investigation strategies assisted by digital storyboard media. The study was carried out in cycles following Kemmis’ cycle process. The subjects of this study were 33 grade X students of SMA Al-Hikmah Medan in 2019/2020 academic year. The data were collected by employing observation, field-note and writing test. After completing the study, the result shows that the implementation of group investigation strategy assisted by digital story board media significantly improved students’ critical thinking in writing. This is represented by the increase of students’ writing achievement, students’ learning activities and teacher’s performance in teaching. In the first cycle, the number of students passing the standard qualifying of writing set by the school was only 13 students (39.39 %) and improved substantially in cycle two reaching 26 students (78.79 %). The students’ learning activity also progressed considerably as presented in the average score from 67.6% in cycle one to 86% in cycle two. Further, the improvement of teacher’ teaching performance between cycle one and cycle two achieved 23.36% or from 66% in cycle one to 89.36%.